INDUSTRIAL BURNERS TESTING AND COMBUSTION EFFICIENCY ANALYSIS - Pimenta, J.; De Lima, L.C.; Duarte, J.B.F.; Macedo, R. M. (Revista de Engenharia Térmica, 2002)
This paper describes experimental procedures and techniques adopted for combustion analysis during the testing of burners for industrial applications. The tests were carried out in the Combustion Technology Laboratory (NTC) of the University of Fortaleza. The NTC facilities are composed basically of experimental testing hall, a monitoring room, a chromatography laboratory and a modeling and simulation studies room. In the lab testing hall, is installed a test bench composed basically of the following parts : a combustion chamber with nominal thermal capacity of 1.000.000 kcal/h, two fully instrumented gas and air supply sections, a gas analyzer for emissions measurement, a panel for monitoring of water supply to combustion chamber coil, a cooling tower for heat delivery of combustion chamber. A data acquisition and control system is available with all the hardware tools for monitoring of the combustion process. With all the acquired measurements of temperature, flow rate, pressures, emissions, etc., the First Law energy balance approach was used in order to evaluate the combustion efficiency of two different burners with 378.000 and 403.200 kcal/h nominal heat power. Analysis of preliminary results allows representing the burners efficiency according to different air and fuel operating conditions. The experimental data obtained are also compared with simulation results from the modeling of the combustion process, presented in another article linked with this work, where a discussion of such comparison is made. Future studies will be dedicated to the development of improved efficiency combustion systems for industrial and commercial applications.